2012
DOI: 10.1111/j.1532-849x.2012.00949.x
|View full text |Cite
|
Sign up to set email alerts
|

FEA Evaluation of the Resistance Form of a Premolar Crown

Abstract: Use of buccolingual convergence angles greater than 12° reduced the resistance form of the preparation. Luting agents capable of delivering strong bonding between the crown and the preparation improved the resistance in highly tapered preparations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…This initial search retrieved many articles that were not relevant to the review, including in vitro bench fatigue tests, strength tests, finite element analyses, and retention analysis using fixed TOC values of 32 degrees or less. [51][52][53][54] Many relevant studies had to be excluded because they reported grouped values or ranges or did not provide enough information. Some of the included articles failed to specify anatomic location (mandible versus maxilla) 29 45 The TOC angle was the most commonly reported parameter.…”
Section: Discussionmentioning
confidence: 99%
“…This initial search retrieved many articles that were not relevant to the review, including in vitro bench fatigue tests, strength tests, finite element analyses, and retention analysis using fixed TOC values of 32 degrees or less. [51][52][53][54] Many relevant studies had to be excluded because they reported grouped values or ranges or did not provide enough information. Some of the included articles failed to specify anatomic location (mandible versus maxilla) 29 45 The TOC angle was the most commonly reported parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional preparation design recommendations were correctly developed in the era of cast metal restorations cemented with aqueous‐based luting agents. The advent of CAD/ CAM coupled with adhesive technology has led to some questioning of traditional preparation recommendations . The purpose of this study was to investigate the effect of bicuspid preparation axial wall height on the fracture mode of adhesively luted CAD/CAM all‐ceramic crowns based on a preparation containing an advanced 20° TOC.…”
mentioning
confidence: 99%
“…The displacement causes tensile stress in the margin and luting agent. The degree of displacement increases with increasing taper angles augmenting the chances of debonding (Bowley et al, 2012). No studies to the authors' knowledge have clinically tested the role of TOC angle with survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Crack initiation in the luting agent due to mechanical failure is likely to initiate at the marginal area and possibly induce debonding of the restoration as it propagates (Bowley et al, 2012). Crack initiation can also occur below the occlusal surface of a posterior crown especially when the gap to be filled by the cement is substantial and resin shrinkage occurs upon curing (Kelly, 1999).…”
Section: Discussionmentioning
confidence: 99%